Sequential injection titration with spectrophotometric detection for the assay of acidity in fruit juices - Jakmunee J. (2014)
A simple sequential injection analysis (SIA) with spectrophotometric detection for an assay of acidity in fruit juice was investigated. An alkaline reagent (sodium hydroxide), a sample and an indicator (phenolphthalein) were first aspirated and stacked as adjacent zones in a holding coil. With flow reversal through a reaction coil to the detector, zone penetration occurred, leading to a neutralization reaction that caused a decrease in the color intensity of the indicator being monitored for absorbance at 552 nm. The effects of various parameters were studied. Linear calibration graphs for acidities of 0.2 - 1.0 and 0.5 - 2.5% w/v citric acid as a standard, with a relative standard deviation of 1% (acidity of 0.3 - 0.6% w/v as citric acid, n=11) and a sample throughput of 30 samples h(-1), were achieved. The developed method was validated by a standard titrimetric method for assaying the acidity of fruit juice samples.